2019
DOI: 10.4314/sajas.v49i2.5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding regime on the performance and blood parameters of male and female broiler chickens

Abstract: The aim of the present study was to evaluate the effect of feeding regime on changes in growth, mortality, carcass composition, and blood parameters of male and female broiler chickens during feed restriction and the realimentation period. In the experiment, males and females were split into three groups: i) ADL, a group fed ad libitum during the entire experiment; ii) R80, a group that received 80% ad libitum; and iii) R65, a group that received 65% ad libitum. Restriction was applied in both groups from 7 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…In addition, pasture access did not have a beneficial effect on the FCR, according to Ponte et al (2008). Feed restriction led to a reduction in mortality, which was only 22% in group 2 and 11% in group 3 in the free-range group compared to that in the AL group; these findings are consistent with those of Mohammadalipour et al (2017), Tumova and Chodova (2018) and Tumova et al (2019). The decreased mortality of restricted chickens is due to a decreased incidence of sudden death syndrome and ascites (Lippens et al 2000;Mohammadalipour et al 2017;Tumova et al 2019) and leg problems (Lippens et al 2000).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…In addition, pasture access did not have a beneficial effect on the FCR, according to Ponte et al (2008). Feed restriction led to a reduction in mortality, which was only 22% in group 2 and 11% in group 3 in the free-range group compared to that in the AL group; these findings are consistent with those of Mohammadalipour et al (2017), Tumova and Chodova (2018) and Tumova et al (2019). The decreased mortality of restricted chickens is due to a decreased incidence of sudden death syndrome and ascites (Lippens et al 2000;Mohammadalipour et al 2017;Tumova et al 2019) and leg problems (Lippens et al 2000).…”
Section: Resultssupporting
confidence: 80%
“…Like those in the gizzard group, the liver proportion in the restricted group increased (P = 0.05), and neither of the restricted groups significantly differed. Tumova et al (2019) observed a greater liver proportion and postulated that this increase is related to greater functional activity and glycogen storage and therefore to increased body fat deposition (Tumova et al 2019).…”
Section: Resultsmentioning
confidence: 99%
“…When the temperature of consumed water is lower than body temperature, which helps to keep the metabolic temperature and increases appetite for water and feed [14]. Cold water intake increases the slaughter weight and average weekly gain [12][13][14][15][16][17][18][19][20][21]. However, in our study, no significant difference was found between slaughtering weights of broilers consumed normal and cold water.…”
Section: Rectal Temperature and Mortalitymentioning
confidence: 79%
“…Actual deaths were within acceptable limits (between 0-1.7%) and evaluated as normal. It was found that intermittent feed and cold water applications did not affect the mortality rate [12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
See 1 more Smart Citation